2017
DOI: 10.1017/s0025315417000601
|View full text |Cite
|
Sign up to set email alerts
|

The euryhaline crabUca tangerishowed metabolic differences to sex and environmental salinity

Abstract: This study constitutes a first attempt to investigate sex differences in osmoregulatory capacity and metabolic responses in relation to hyper- and hypo-osmoregulation in the intertidal euryhaline crab Uca tangeri. Adult male and female specimens from Cadiz Bay, Spain (36°23′–37′N 6°8′–15′W), were acclimated to three different environmental salinities (12, 33 and 55 psu) during 7 days, and several parameters were assessed in haemolymph (osmolality, glucose, amino acids, triglycerides and lactate) as well as in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…Low salinity may greatly affect the fatty acid composition of P. trituberculatus by influencing the osmoregulation mechanism (Ran et al, 2017;Romano et al, 2014;Sarker et al, 2011). There are also evidence show that low salinity can influence the process of physiological metabolism of muscles and other tissues in marine species and then change the nutritional composition of them (Pinoni et al, 2018;Romano et al, 2014). Results showed that in total, 14 kinds of PUFAs and MUFAs were detected in both low salinity group and control group, with total amount accounts for 75.13% and 74.64% in total fatty acid respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Low salinity may greatly affect the fatty acid composition of P. trituberculatus by influencing the osmoregulation mechanism (Ran et al, 2017;Romano et al, 2014;Sarker et al, 2011). There are also evidence show that low salinity can influence the process of physiological metabolism of muscles and other tissues in marine species and then change the nutritional composition of them (Pinoni et al, 2018;Romano et al, 2014). Results showed that in total, 14 kinds of PUFAs and MUFAs were detected in both low salinity group and control group, with total amount accounts for 75.13% and 74.64% in total fatty acid respectively.…”
Section: Discussionmentioning
confidence: 99%
“…trituberculatus . Several researches have already investigated in other aquatic animals about the impact of low salinity on fatty acid, for example, mud crab Scylla serrata (Romano et al, 2014), mud crab Scylla paramamosain (Wu et al, 2019) and fiddler crab Uca tangeri (Pinoni et al, 2018). However, as little attention was paid to fatty acid composition differences of P .…”
Section: Introductionmentioning
confidence: 99%
“…Changes at molecular and biochemical levels such as those in enzymes and system transports components of the branchial osmoregulatory machine during biochemical adaptation to salinity often requires the mobilization of energy substrates to metabolically deal with salinity challenge (Pinoni et al, 2013;Larsen et al, 2014). This could lead to changes in carbohydrate, lipids, and/or protein metabolism and then to a differential utilization of energy reserves in various storage organs (Pinoni et al, 2013(Pinoni et al, , 2017. The maintenance of glycemia in C. angulatus suggest that availability of glucose from the hemolymph would not be a constraint upon acclimation to different environmental salinities in this crab.…”
Section: Discussionmentioning
confidence: 99%
“…In estuaries and coastal lagoons, intertidal euryhaline crabs must deal with sharp and broad changes in environmental salinity. Biochemical adaptation to environmental salinity implies adjustments in different tissues (Michiels et al, 2013(Michiels et al, , 2015aPinoni et al, 2013Pinoni et al, , 2017Larsen et al, 2014). In intertidal euryhaline crabs, simultaneous determinations of diverse parameters in different organs are needed for an integral analysis of the adaptation at biochemical level to different salinities (Romano and Zeng, 2012;Pinoni et al, 2013Pinoni et al, , 2015.…”
Section: Introductionmentioning
confidence: 99%
“…In response to high osmotic stress, O. aureus excretes excess water into the environment, resulting in a lower moisture content in the muscles compared to freshwater species. Tis is in contrast to marine organisms that adapt to low osmotic pressure, such as Uca tangeri crabs, Scylla paramamosain mud crabs, and Sinonovacula constricta [29][30][31]. When fsh experience salinity-induced stress, ash content plays a crucial role in regulating osmotic ions.…”
Section: Efects Of Salinity On the Physical Properties And Proximatementioning
confidence: 99%